Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Find the two solutions to the equation:
[tex]\[ (x-9)(x+5)=0 \][/tex]


Sagot :

To find the solutions to the equation [tex]\((x-9)(x+5) = 0\)[/tex], we need to solve for [tex]\(x\)[/tex] by setting each factor equal to zero. This method is based on the Zero Product Property, which states that if the product of two factors is zero, at least one of the factors must be zero.

1. Set the first factor equal to zero:
[tex]\[ x - 9 = 0 \][/tex]

Solve for [tex]\(x\)[/tex]:
[tex]\[ x = 9 \][/tex]

So, one solution is [tex]\(x = 9\)[/tex].

2. Set the second factor equal to zero:
[tex]\[ x + 5 = 0 \][/tex]

Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -5 \][/tex]

So, another solution is [tex]\(x = -5\)[/tex].

Thus, the two solutions to the equation [tex]\((x-9)(x+5) = 0\)[/tex] are [tex]\(\boxed{9 \text{ and } -5}\)[/tex].